Achievement of BLU financial performance in the field of education services before and during the COVID-19 pandemic - Rizka Furqorina; Mohammad Iqbal Firdaus (Jurnal Mantik, 2023)
This study aims to determine the performance achievements of the Public Service Agency (BLU) tertiary institution in the Education Services Sector before and during the Covid-19 Pandemic. This study uses secondary data in the form of audited financial reports from 16 BLU Education Service Agencies under Kemendikbudristek. BLU performance measurement uses the achievement score ratio in accordance with the Regulation of the Director General of Treasury Number PER.32/PB/2014 concerning Guidelines for Evaluating the Performance of Public Service Agencies in the Field of Education Services. The ratios used are cash ratio (RK), current ratio (RL), collection period (PPP), fixed asset turnover (PAT), return on fixed assets (ROFA), return on equity (ROE), and the ratio of income to operating expenses (POBO). To find out the performance achievement is done by calculating the ratio and then given a score according to the criteria of Perdirjen PER.32/PB/2014. The financial performance achievements were then compared with the performance achievements before the Covid-19 Pandemic. The statistical test used is the paired sample t-test. The results of this study indicate that there are differences in BLU performance in the field of education services before and during the Covid-19 pandemic. This difference can be seen in the t-test for the ratios of RK, RL, PPP, PAT, POBO, and the Total Score of Financial Performance Achievements. ROFA and ROE ratios do not show significant results. This was due to financial conditions before the pandemic, policy changes during the pandemic, and the response of the BLU in the Education Services Sector to the pandemic.